CFD Analysis into the Drag Estimation of Smooth and Roughened Surface Due to Marine Biofouling - Baital, Muh. Sawal; Utama, I Ketut Aria Pria (IPTEK The Journal for Technology and Science, 2025)
This study is to investigate drag on ship due to marine biofouling using CFD approach. A cargo ship with one year operation was used for the study and to examine the effect of biofouling between smooth and roughened hull by observing the result of CFD simulation. Simulation is done using CFD software based RANSE code together with SST based k-omega as turbulence setting and Grid Generator was used to build the hybrid grids. The result indicated that marine biofouling make significant increase for ship resistance up to 37 %. This fact is in good agreement with experimental test has been examined that fouling increases drag up to 80 % for two years.